A novel cascade latent heat thermal energy storage system consisting of erythritol and paraffin wax for deep recovery of medium-temperature industrial waste heat. (15th February 2023) - Yang, Sheng; Shao, Xue-Feng; Luo, Jia-Hao; Baghaei Oskouei, Seyedmohsen; Bayer, Özgür; Fan, Li-Wu
Abstract: Recovering medium-temperature (e.g., 150–180 °C) industrial waste heat through latent heat thermal energy storage (LHTES) can effectively attenuate the consumption of fossil fuels. However, the LHTES system containing a single medium-temperature phase change material (PCM), e.g., erythritol, cannot absorb the part of heat below the PCM's melting point (∼118 °C) during the charging process. Meanwhile, a single low-temperature PCM, e.g., paraffin wax, is unable to supply a significant amount of heat at temperatures higher than its melting point upon discharging. Therefore, a cascade LHTES system combining one erythritol unit and two paraffin wax units (melting point of ∼60 °C) was proposed to deeply recover the waste heat during charging and increase the heat supply temperature during discharging. Through prototype testing, the performance of such a cascade system was examined under various working conditions. It was shown that the cascade system could improve the efficiency of the waste heat recovery from 15.8% to 63.4% under the charging condition of 100 L/h and 160 °C, as compared to a single-stage erythritol-based system. The average heat supply temperature of the cascade system was also increased from 37 °C (at a constant flow rate) to 53.6 °C via an active discharging strategy (by tuning the flow rate). This highly efficient cascade LHTES system has great potential for recovery of medium-temperature waste heat towards a decarbonized future of space heating for buildings. Highlights: A cascade LHTES system was proposed using paraffin and erythritol for waste heat recovery. The recovery efficiency of 150–180 °C waste heat was improved from only ∼16% to >60%. The average heating supply temperature was increased from only 37 °C to above 53 °C. The part of heat (>60 °C) discharged was increased from 17% to 80% with this cascade design. This novel system will contribute to a decarbonized future of space heating for buildings.